Cloud Based Collaborative Workspace: Communication Channel, Video Conferencing, Voice Messaging, File Sharing - Vina S. Barsawade,; Samiksha V. Patil,; Pranali M. Khatkale,; Shweta R. Chakur,; Ishwari R. Madane,; Nimisha. D. Deval, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
With the growing demand for efficient and versatile tools in the modern workplace, this project introduces a cloud-based collaborative workspace designed to integrate key communication and productivity features. The platform offers seamless communication channels, including video conferencing, voice messaging, and real-time chat, while enabling secure file sharing and streamlined workflows. By leveraging cloud technology, the system ensures accessibility from any location, fostering collaboration among remote and distributed teams. Its unified interface eliminates the need for multiple tools, reducing inefficiencies and enhancing productivity. The platform also supports dynamic team interactions, enabling users to stay connected and share resources effortlessly. Designed with a focus on security and scalability, this project aims to address the challenges of remote work environments by providing a robust, all-in-one solution to enhance team collaboration, improve communication flow, and support efficient task management. This initiative paves the way for more cohesive and connected workspaces in a digital-first era.